Cascading Effects of Birds and Bats in a Shaded Coffee Agroforestry System - Schmitt, Lauren; Greenberg, Russell; Ibarra-Núñez, Guillermo; Bichier, Peter; Gordon, Caleb E.; Perfecto, Ivette (Frontiers in Sustainable Food Systems, 2021)
Volant vertebrate insectivores, including birds and bats, can be important regulators of herbivores in forests and agro-ecosystems. Their effects can be realized directly through predation and indirectly via intraguild predation. This paper examines data from bird and bat exclosures in coffee farms in Chiapas, Mexico in order to determine their effect on herbivores. Arthropods were sampled in 32 exclosures (with 10 coffee plants in each) and their paired controls three times during 6 months. After 3 months, herbivore and spider abundance increased, underscoring the importance of both intertrophic predation between volant vertebrate insectivores and herbivores and intraguild predation between volant vertebrate insectivores and spiders. After 6 months, herbivore abundance increased in the exclosures, which is indicative of a direct negative effect of birds and bats on herbivores. We suggest that intraguild predation is important in this food web and that seasonality may change the relative importance of intraguild vs. intertrophic predation. Results suggest a dissipating trophic cascade and echo the growing body of evidence that finds birds and bats are regulators of herbivores in agro-ecosystems.